Prevalence of ciguatoxins in lionfish (Pterois spp.) from Guadeloupe, Saint Martin, and Saint Barthélmy Islands (Caribbean). (August 2015) - Soliño, Lucía; Widgy, Saha; Pautonnier, Anthony; Turquet, Jean; Loeffler, Christopher R.; Flores Quintana, Harold A.; Diogène, Jorge
Abstract: Lionfish ( Pterois spp.) are invasive species that have recently spread throughout the Caribbean. Lionfish are available for purchase in local markets for human consumption in several islands of the region. We examined the prevalence of ciguatoxins (CTXs) in lionfish from the French Antilles, a ciguatera-endemic region. The neuroblastoma-2a (N2a) cell assay was used to assess composite cytotoxicity in 120 fish samples collected from the surrounding waters of Guadeloupe (n = 60), Saint Barthélemy Islands (n = 55) and Saint Martin (n = 5). Twenty-seven of these samples exhibited CTX-like activity by the N2a assay. Ciguatoxin (CTX) was confirmed by liquid chromatography-tandem mass spectrometry (LC-MS/MS) in multiple samples that presented highest composite toxicity levels by N2a. Those fish found to contain CTXs were all from Saint Barthélemy. Lionfish from Guadeloupe and Saint Martin did not exhibit toxin activity, although the sample size from Saint Martin was insufficient to draw any conclusions as to the incidence of CTXs. In this study, we provide information about the potential hazard of ciguatera associated with the consumption of lionfish from known endemic areas. We also demonstrate the utility of the cell-based assay combined with LC-MS/MS to assess activity and to provide structural confirmation of CTXs respectively. Highlights: The prevalence of ciguatoxins (CTXs) in lionfish from the French Antilles was confirmed for the first time. Lionfish have the potential to be a vector for CFP. The cell-based assay is a useful tool to detect CTX activity combined with LC-MS/MS for confirmation of CTXs.